The cost of racism for people of color: contextualizing experiences of discrimination - Alvarez, Alvin N.; Liang, Christopher T. H.; Neville, Helen A. (Cultural, racial, and ethnic psychology book series, 2016)
Introduction -- Theoretical and methodological foundations -- A theoretical overview of the impact of racism on people of color / Alex Pieterse and Shantel Powell -- Applying intersectionality theory to research on perceived racism / Jioni A. Lewis and Patrick R. Grzanka -- Improving the measurement of perceived racial discrimination : challenges and opportunities / David R. Williams -- Moderators and mediators of the experience of perceived racism / Alvin Alvarez, Christopher T. H. Liang, Carin Molenaar, and David Nguyen -- Context and costs -- Racism and mental health : examining the link between racism and depression from a social-cognitive perspective / Elizabeth Brondolo, Wan Ng, Kristy-Lee J. Pierre, and Robert Lane -- Racism and behavioral outcomes over the life course / Gilbert C. Gee and Angie Denisse Otiniano Verissimo -- Racism and physical health disparities / Joseph Keaweaimoku Kaholokula -- The impact of racism on education and the educational experiences of students of color / Adrienne D. Dixson, Dominique Clayton, Leah Peoples, and Rema Reynolds -- The costs of racism on workforce entry and work adjustment / Justin C. Perry and Lela L. Pickett -- The impact of racism on communities of color : historical contexts and contemporary issues / Azara L. Santiago Rivera, Hector Y. Adames, Nayeli Y. Chavez-Dueñas, and Gregory Benson-Flórez -- Interventions and future directions -- Racial trauma recovery : a race-informed therapeutic approach to racial wounds / Lillian Comas-Díaz -- Critical race, psychology and social policy : refusing damage, cataloguing oppression, and documenting desire / Michelle Fine and William E. Cross -- Educational interventions for reducing racism / Elizabeth Vera, Daniel Camacho, Megan Polanin, and Manuel Salgado -- Toward a relevant psychology of prejudice, stereotyping and discrimination : linking science and practice to develop interventions that work in community settings / Ignacio D. Acevedo-Polakovich, Kara L. Beck, Erin Hawks, and Sarah E. Ogdie